Visible-Light Photoredox Borylation of Aryl Halides and Subsequent Aerobic Oxidative Hydroxylation - Jiang, Min; Yang, Haijun; Fu, Hua (Organic letters, 2016)
Efficient and practical visible-light photoredox borylation of aryl halides and subsequent aerobic oxidative hydroxylation were developed. The protocols use readily available aryl halides and bis(pinacolato)diboron as the starting materials, fac-Ir(ppy)3 as the photocatalyst, and corresponding arylboronic esters and phenols were obtained in good yields. The methods show some advantages including simple equipment, mild conditions, easy operation, and wide substrate scope. Therefore, they should provide a valuable strategy for chemical transformations.